2023
DOI: 10.3390/polym15051307
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances in Degradation of Polymer Plastics by Insects Inhabiting Microorganisms

Abstract: Plastic pollution endangers all natural ecosystems and living creatures on earth. Excessive reliance on plastic products and excessive production of plastic packaging are extremely dangerous for humans because plastic waste has polluted almost the entire world, whether it is in the sea or on the land. This review introduces the examination of pollution brought by non-degradable plastics, the classification and application of degradable materials, and the current situation and strategy to address plastic pollut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 57 publications
0
7
0
1
Order By: Relevance
“…T. molitor and its gut microbiota degrade polystyrene (PS), polyvinyl chloride (PVC), polyethylene (PE), acrylonitrile butadiene styrene (ABS), polyurethane (PU), bio-based cross-linked polymers, and other plastic polymers ( 75 ). Research findings have identified eight specific microorganisms responsible for polystyrene biodegradation in T. molitor : Citrobacter freundii, Klebsiella aerogenes, S. marcescens, Stenotrophomonas maltophilia, Bacillus thuringiensis, P. aeruginosa, Enterococcus faecalis , and Enterobacter asburiae.…”
Section: Insect Gut Microbiotamentioning
confidence: 99%
“…T. molitor and its gut microbiota degrade polystyrene (PS), polyvinyl chloride (PVC), polyethylene (PE), acrylonitrile butadiene styrene (ABS), polyurethane (PU), bio-based cross-linked polymers, and other plastic polymers ( 75 ). Research findings have identified eight specific microorganisms responsible for polystyrene biodegradation in T. molitor : Citrobacter freundii, Klebsiella aerogenes, S. marcescens, Stenotrophomonas maltophilia, Bacillus thuringiensis, P. aeruginosa, Enterococcus faecalis , and Enterobacter asburiae.…”
Section: Insect Gut Microbiotamentioning
confidence: 99%
“…Increasing world population has led to increased production and consumption of plastic materials. However, the accumulation of petrol-plastic wastes in the environment has become the focus of worldwide attention because of the environmental problems caused by their improper disposal after use and decommissioning and because the natural degradation of plastics is very sluggish, resulting in the accumulation of plastic waste that poses a serious environmental threat [2][3][4]. 2 The main disposal methods include landfill, incineration, chemical treatment, and recycling.…”
Section: Introductionmentioning
confidence: 99%
“…Considering that much plastic waste has not been scientifically and properly treated, through a series of physical and chemical processes, microplastics are formed and dispersed into the environment [3,6]. Furthermore, organisms can interact with plastic waste: several species of vertebrates and invertebrates have been reported to ingest or become entangled in plastic as animals are unable to distinguish food from plastic in the environment, resulting in the ingestion of plastic particles [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…However, the large amount of consumption inevitably brings a large amount of recycling problems. Many waste plastics were not treated scientifi cally and correctly, they form Microplastics (MPs) through a series of physical and chemical processes and enter the ocean [1]. In recent years, Microplastics (MPs) have been widely distributed in marine and coastal waters around the world, causing serious pollution to marine ecosystems [2,3].…”
Section: Introductionmentioning
confidence: 99%